Digital Revolution in the Kurdistan Region: Challenges and Opportunities (Global Journal of Management and Business Research, 2025)
The Kurdistan Region in Iraq (KRI) stands at a pivotal moment, where digital transformation has the potential to reshape governance, the healthcare sector, education, and local governments, while driving economic growth. Recent actions by the Kurdistan Regional Government (KRG), such as the Digital Transformation Strategy and the Prime Minister’s commitment to e-governance and smart cities, demonstrate a political will to harness information and communication technologies (ICT) for sustainable development. However, institutional divisions, cultural differences, skills gaps, infrastructural and technological limitations, ecosystem challenges, and societal readiness pose significant challenges. Based on recent scholarship on smart cities, higher education, and public sector reforms, along with policy announcements and regional analyses, this paper critically examines the challenges and prospects of Kurdistan’s digital revolution, drawing on current research, policy documents, and regional case studies. The research concludes that successful digital transformation requires an integrated framework that combines institutional leadership, citizen engagement, international cooperation, and investment in infrastructure.